Prevalence of Enterococci Infection in Blood Cultures Based on Age Group at Makerere University Clinical Microbiology Laboratory. A Cross-Sectional Study. - Nashibula, Daisy; Asia Mustafah (Student’s Journal of Health Research Africa, 2022)
Background: Aminoglycoside resistance has been of great concern since it eliminates the synergy of aminoglycosides with beta-lactam antibiotics, which is the therapy of choice for most enterococcal infections and can limit the therapeutic options for clinicians. Although enterococci are not virulent as other gram-positive bacteria, they are multidrug-resistant which restricts the clinician’s options for treatment of the enterococcal infections. The objective of this study is to determine the Prevalence of Enterococci Infection in Blood Cultures Based on Age Group at Makerere University Clinical Microbiology Laboratory. Methodology: The study was a retrospective cross-sectional study on the evaluation of high-level aminoglycoside resistance of enterococcal isolates in blood culture at MUCML between January 2017 and December 2020. Results: The prevalence of enterococcal species was 6.07%, from these 66.67% were found to be among children between 0 and 5 years of age. A total number of 2176 were positive blood cultures between the year 2017 to 20202 at Makerere University Clinical Microbiology Laboratory. Of these 132 blood cultures were Enterococci positive with a percentage prevalence of 6.07%. The most prevalent organism was Coagulase-negative staphylococci with a total number of 667 (30.65%) organisms and the least prevalent was Proteus Mirabilis with a total number of 4 (0.18%). Conclusion: The study found that ages between 0 to 5 years had the highest incidence of enterococcal infections and the occurrence of these infections increased with the years. Recommendation: Since the highest infections occurred between the ages 0 to 5 years, this showed that the infection was nosocomial and hence doctors should adhere to infection prevention and control protocols when handling patients.